2016
DOI: 10.3847/0067-0049/225/1/9
|View full text |Cite
|
Sign up to set email alerts
|

Transit Timing Observations From Kepler. Ix. Catalog of the Full Long-Cadence Data Set

Abstract: We present a new transit timing catalog of 2599 Kepler Objects of Interest (=KOIs), using the PDC-MAP long-cadence light curves that include the full seventeen quarters of the mission (ftp://wise-ftp.tau.ac.il/pub/tauttv/TTV/ver 112).The goal is to produce an easy-to-use catalog that can stimulate further analyses of interesting systems. For 779 KOIs with high enough SNRs, we derived the timing, duration and depth of 69,914 transits. For 1820 KOIs with lower SNR, we derived only the timing of 225,273 transits.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
330
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(354 citation statements)
references
References 63 publications
20
330
1
Order By: Relevance
“…I found clearly non-sinusoidal TTVs for Kepler-448/KOI-12b, Kepler-693/KOI-824b, and Kepler-419/KOI-1474b. The result is consistent with the TTV search by Holczer et al (2016), who reported significant long-term TTVs for the same three KOIs in our sample.…”
Section: Systematic Ttv Search For Singly-transiting Warm Jupiterssupporting
confidence: 93%
“…I found clearly non-sinusoidal TTVs for Kepler-448/KOI-12b, Kepler-693/KOI-824b, and Kepler-419/KOI-1474b. The result is consistent with the TTV search by Holczer et al (2016), who reported significant long-term TTVs for the same three KOIs in our sample.…”
Section: Systematic Ttv Search For Singly-transiting Warm Jupiterssupporting
confidence: 93%
“…While ≈40% of Kepler planets are in multi-planet systems (Rowe et al 2014), planets typically need to be near mean-motion resonance to produce detectable TTVs. Holczer et al (2016) reported TTVs for ≈260 Kepler planets, but most are too faint for precision RV measurements with currentgeneration instruments, which typically require host stars with  V 13 mag. As a result, fewer than 10 systems have mass constraints from both the TTV and the RV techniques (Mills & Mazeh 2017).…”
Section: Introductionmentioning
confidence: 99%
“…While we performed the TTV analysis of this data set after it has been published, we did not make an extensive use of the results. Our orbital models derived on the basis of the (Rowe et al 2015) catalogue fit the TTV time-series in Holczer et al (2016) as well. We have got qualitatively the same distributions of the best-fitting parameters.…”
Section: The Ttv Data Model and Optimisationmentioning
confidence: 77%
“…Such a TTV variability is relatively clear as compared to other 2-planet systems in the KEPLER sample published in the (Rowe et al 2015) catalogue. Recently, Holczer et al (2016) performed a new re-analysis of the KEPLER data and they report 162 measurements for Kepler-29 that cover both the long-cadence and, when available, short-cadence KEPLER light-curves. While we performed the TTV analysis of this data set after it has been published, we did not make an extensive use of the results.…”
Section: The Ttv Data Model and Optimisationmentioning
confidence: 99%
See 1 more Smart Citation